Implementation Interpreter Role in Investigations Process at the Ditpolairud Polda Kepri - Frangky Silitonga; Marthin Edi Candra Simarmata; Haerul Umami; Kartika Cahayani; Christina Koh; Agung Edy Wibowo (LPPM-IAI Hidayatullah Batam, 2026)
The Riau Islands Province, as an international border region, experiences a high intensity of maritime activities, making it vulnerable to various forms of transnational crimes. The Directorate of Water and Air Police (Ditpolairud) of the Riau Islands Regional Police frequently handles cases involving foreign nationals. One of the main obstacles in the investigation process is language barriers. Therefore, the assistance of English interpreters plays a crucial role in accelerating and facilitating the investigation process. This community service activity aims to enhance the capacity of interpreters and Gakkum Ditpolairud personnel in supporting effective case investigations. The methods applied include training, direct assistance, case simulations, and evaluations. The results indicate that interpreter assistance improves investigation time efficiency, enhances the quality of official investigation reports, and strengthens the juridical aspects of cases. This activity makes a tangible contribution to improving professionalism and accountability in maritime law enforcement at Ditpolairud of the Riau Islands Regional Police.